Design and Analysis of A Pre-Engineered Warehouse Building Considering Lateral Load Using ETABS A Review - Anuj Kumar; Afzal Khan; Vikas Patidar (International Journal of Scientific Research in Civil Engineering, 2021)
Pre Engineered Building (PEB) concept in the design of structures has helped in optimizing design. Steel is the basic material that is used in the Materials that are used for Pre-engineered steel building. The latest version of the Code of Practice for general construction in steel IS 800:2007 is based on Limit State Method of design . The adoptability of PEB in the place of Conventional Steel Building (CSB) design concept resulted in many advantages, including economy and easier fabrication. Long Span, Column free structures are the most essential in any type of industrial structures and Pre Engineered Buildings (PEB) fulfills this requirement along with reduced time and cost as compared to conventional structures. PEB methodology is versatile not only due to its quality pre-designing and prefabrication, but also due to its light weight and economical construction. In this study, an industrial structure (Ware House) is analyzed and designed according to the Indian standard, IS 800-2007. The study of Pre Engineering Building with Conventional Steel Building has been carried out and the observations made based on this study are very much useful to the practicing structural engineers. In this paper we are presenting review of literatures.
Keywords: Steel Structure; Conventional Steel Building (CSB); Pre Engineered Building (PEB); Bracing Systems; Wind Analysis; Cross Bracing; Diagonal Bracing; K-Bracing